hidden mistake

by limitkiller
Tags: hidden, mistake
 P: 72 that is too sad it have been 2 days and i coudnt find out where do i make mistake. i wanted to prove:" (f(x)*g(x))'= g(x)*f(x)'+ g(x)'*f(x)". so: (f(x)*g(x))'= lim h→0 ((f(x+h)*g(x+h)-f(x)*g(x))/h) =lim h→0 ((f(x+h)*g(x+h))/h) - lim h→0 (f(x)*g(x))/h) =[lim h→0 ((f(x+h))/h)*lim h→0 (g(x+h))] - [ lim h→0 ((f(x))/h) * lim h→0 (g(x))] =[lim h→0 ((f(x+h))/h)* g(x)] - [ lim h→0 ((f(x))/h) * (g(x)] = g(x)*[lim h→0 ((f(x+h))/h) - lim h→0 ((f(x))/h)] = g(x)*[lim h→0 ((f(x+h)-f(x))/h)] = g(x)*f(x)' then (f(x)*g(x))'= g(x)*f(x)' !(?)!
 Sci Advisor P: 1,670 The limits lim h→0 ((f(x+h))/h) and lim h→0 ((f(x))/h) does not necessarily exist.
 PF Patron HW Helper Sci Advisor Thanks P: 11,935 Hint: $$0=f(x+h)g(x)-f(x+h)(gx)$$
PF Patron
P: 864

hidden mistake

Just to expand on what other people have said, rules like "The limit of the difference is the difference of the limits" only apply when both limits exist. So it is not true that
$$\lim_{h\to 0}\frac{f(x+h)g(x+h)-f(x)g(x)}{h}= \lim_{h\to 0}\frac{f(x+h)g(x+x)}{h} -\lim_{h\to 0}\frac{f(x)g(x)}{h} = \infty - \infty$$
(the last equality is assuming neither f nor g is 0 or has a 0 limit at x)
Likewise, splitting up limits like that only works when the limits each exist for addition, multiplication and division. The limit of the denominator also can't be 0 in the case of division.
 P: 72 thanks that was so silly.

 Related Discussions Advanced Physics Homework 0 High Energy, Nuclear, Particle Physics 2 Computers 14 General Physics 40